2021
DOI: 10.1038/s41467-021-24888-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a sudden increase in the nuclear size of proton-rich silver-96

Abstract: Understanding the evolution of the nuclear charge radius is one of the long-standing challenges for nuclear theory. Recently, density functional theory calculations utilizing Fayans functionals have successfully reproduced the charge radii of a variety of exotic isotopes. However, difficulties in the isotope production have hindered testing these models in the immediate region of the nuclear chart below the heaviest self-conjugate doubly-magic nucleus 100Sn, where the near-equal number of protons (Z) and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…High-precision measurements of nuclear charge radii offer unique information on the structure of atomic nuclei and fundamental symmetries of nature [1,2]. In particular, the precise data on variations of charge radii with proton and neutron numbers shed light on elusive aspects of nuclear behavior, such as superfluidity [3][4][5][6], shell structure [7,8], and correlations [9,10].…”
mentioning
confidence: 99%
“…High-precision measurements of nuclear charge radii offer unique information on the structure of atomic nuclei and fundamental symmetries of nature [1,2]. In particular, the precise data on variations of charge radii with proton and neutron numbers shed light on elusive aspects of nuclear behavior, such as superfluidity [3][4][5][6], shell structure [7,8], and correlations [9,10].…”
mentioning
confidence: 99%
“…Recent high-precision measurements of charge radii in isotope chains of potassium [17], calcium [18,19], nickel [20], copper [21,22], and silver [23], have revealed that they carry information about changes in shell-structure, deformation, and pairing effects. Charge radii can be easily probed with the well-known electromagnetic interaction [24,25].…”
mentioning
confidence: 99%
“…Overall, all functionals describe the correct general smooth parabolic behavior of the measured radii, but Fy(std) underestimates the absolute charge radii, especially with respect to the neutron-rich isotopes. FyðΔr; HFBÞ is the only functional which reproduces the correct direction of the OES pattern where measured values are available, although the staggering is overestimated somewhat, a feature which has also been observed in other isotopic chains [11,12,16,18]. The other two functionals tend to underestimate the staggering or even show reversed OES compared to the measured values, and also in the predictions for other odd-A isotopes.…”
mentioning
confidence: 50%
“…This EDF was reoptimized within the Hartree-Fock-Bogoliubov (HFB) framework, resulting in the new FyðΔr; HFBÞ EDF [10,17]. It has been applied successfully to describe the charge radii of weakly bound proton-rich Ca nuclei [10]; to reproduce the kinks in the charge radii of Sn isotopes at the N ¼ 82 shell closure [7] and in the charge radii of Ag isotopes at N ¼ 50 [18]; to investigate the oddeven staggering (OES) in the charge radii of Cu isotopes [11]; and to reproduce the charge radii of K isotopes [12]. So far, all of these studies were performed close to shell closures, and thus in (mainly) spherical nuclei.…”
mentioning
confidence: 99%